STRATEGIC VECTOR OF UKRAINE’S CUSTOMS POLICY IN CONDITIONS OF INSTABILITY - Чорна, Т.О. (SWorldJournal, 2025)
Contemporary Ukraine is experiencing exceptionally challenging conditions, unprecedented since the country gained independence — namely, the full-scale military invasion by the russian federation. In this context, reinforcing the European integration traj